Evaluation of quality of life in type-2 diabetes with other comorbid conditions: a cross-sectional study - Sreya Kosanam; Nithya Varadarajan; Aman Suresh Tharayil; Hari Chandana Varikallu; M. Sai Sruthi (Discover Public Health)
Abstract Objective The objective of this research was to compare the quality of life for diabetics and other co-morbidities (DM with Hypertension, DM with Thyroid Disease, DM with Kidney Disease and DM with Cancer). Methods A cross-sectional descriptive study was conducted at tertiary care hospitals in Andhra Pradesh, India, which included three study centers to assess the QoL of patients with T2DM. Quality of life (QoL) was assessed using the patient demographic details, family history, and laboratory parameters (BP, GRBs, and HbA1c). Short Form-36 (SF-36) questionnaire Informed consent was obtained from the patient and the SF36 score was calculated using the SF-36 score calculator. The QoL of the comorbidity group was compared that with of diabetes patients with no comorbidities. Results A total of 250 subjects were included from age groups of > 18 years and < 85 years. Most of them were age group–40 to 64. The QoL in patients with diabetes alone was higher (54.26%) than that in patients with diabetes and kidney disease (53.21%), diabetes with hypertension (52.16%), and diabetes with thyroid (43.16%), whereas diabetes with cancer had a very low QOL (39.5%). Conclusion According to 8 parameters included in SF 36, diabetes patients have high Quality of Life (QOL) (54.26%) in Physical functioning (PF), role-physical (RP), bodily pain (BP), general health (GH), vitality (VT), social functioning (SF), role-emotional (RE), and mental health (MH). We observed a positive impact on QOL (53.15%) in patients with Diabetes (DM) other co-morbid conditions had equal QOL (52.16) even though some of the variables that were related with QOL (such as age, gender, and ethnicity) cannot be changed.